Safety and complexity: the inter-departmental threats to patient safety in the operating department - Waring, Justin; McDonald, Ruth; Harrison, Stephen (Emerald, 2006)
Purpose: Current thinking about ‘patient safety’ emphasises the causal relationship between the work environment and the delivery of clinical care. This research draws on the theory of Normal Accidents to extend this analysis and better understand the ‘organisational factors’ that threaten safety. Methods: Ethnographic research methods were used, with observations of the operating department setting for 18 month and interviews with 80 members of hospital staff. The setting for the study was the Operating Department of a large teaching hospital in the North-West of England. Results: The work of the operating department is determined by inter-dependant, ‘tightly coupled’ organisational relationships between hospital departments based upon the timely exchange of information, services and resources required for the delivery of care. Failures within these processes, manifest as ‘breakdowns’ within inter-departmental relationships lead to situations of constraint, rapid change and uncertainty in the work of the operating department that require staff to break with established routines and work with increased time and emotional pressures. This means that staff focus on working quickly, as opposed to working safely. Conclusion: Analysis of safety needs to move beyond a focus on the immediate work environment and individual practice, to consider the more complex and deeply structured organisational systems of hospital activity. For departmental managers the scope for service planning to control for safety may be limited as the structured ‘real world’ situation of service delivery is shaped by inter-department and organisational factors that are perhaps beyond the scope of departmental management.